THE EFFECTS OF PERFORMANCE TARGETS AND TRANSFER POLICY PERCEPTIONS ON EMPLOYEE PERFORMANCE THROUGH WORK MOTIVATION AT THE BANDAR LAMPUNG TWO PRIMARY TAX OFFICE - Bowo, Bayu Ari; Aminah, Aminah (PT. Hasba Edukasi Mandiri, 2026)
Employee performance plays an important role in achieving organizational objectives, particularly in government institutions that implement performance management systems based on predetermined targets. This study examines the effects of Performance Targets and Perceptions of the Transfer Policy on Employee Performance, both directly and indirectly through Work Motivation as a mediating variable at the Bandar Lampung Dua Primary Tax Office. A quantitative approach with a cross-sectional survey design was employed. The study involved 88 employees, all of whom were selected as respondents using a saturated sampling technique. Data were collected through a Likert-scale questionnaire and analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS). The conceptual framework was grounded in Vroom’s Expectancy Theory. The results demonstrate that Performance Targets have a positive and significant effect on Employee Performance, with a path coefficient of 0.457, while Perceptions of the Transfer Policy also have a positive and significant effect on Employee Performance, with a coefficient of 0.453. Performance Targets positively and significantly affect Work Motivation, with a coefficient of 0.406, while Perceptions of the Transfer Policy have a coefficient of 0.508. Furthermore, Work Motivation has a positive and significant effect on Employee Performance, with a coefficient of 0.330. The mediation analysis reveals that Work Motivation mediates the effect of Performance Targets on Employee Performance, with an indirect effect of 0.134, and also mediates the effect of Perceptions of the Transfer Policy on Employee Performance, with an indirect effect of 0.168. Both relationships demonstrate complementary partial mediation. These findings indicate that clear and attainable performance targets, together with positive perceptions of transfer policies, can strengthen employees’ work motivation and subsequently contribute to improved performance. Therefore, performance targets should be established in a measurable and realistic manner, while employee transfer policies should be implemented fairly, transparently, consistently, and based on competencies to create working conditions that foster employee motivation and performance.